2019
DOI: 10.1016/s1569-9056(19)31621-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the tumor thrombus from the right atrium without extracorporeal circulation: Emphasis on the displacement of the tumor apex

Abstract: Objectives. To assess the outcomes of cavoatrial tumor thrombus removal using the liver transplantation technique for thrombectomy, a retrospective study was conducted. Materials and Methods. Five patients with atrial tumor thrombi who underwent piggyback mobilization of the liver, surgical access to the right atrium from the abdominal cavity, and external manual repositioning of the thrombus apex below the diaphragm (milking maneuver) were included into the study. Extracorporeal circulation was used in none o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…8,18,20,22 We also compared the results of the current study with other studies in literature that used open surgery without CPB and a clamp below the atrium for 4a thrombi (Table 4). 8,18,20,22-25 The results showed that RA-IVCT, using an intrapericardial control technique without CPB was comparable with open approach in surgical and survival outcomes. However, due to the small sample size and selection bias, we should be more tempered in this conclusion.…”
Section: Discussionmentioning
confidence: 94%
“…8,18,20,22 We also compared the results of the current study with other studies in literature that used open surgery without CPB and a clamp below the atrium for 4a thrombi (Table 4). 8,18,20,22-25 The results showed that RA-IVCT, using an intrapericardial control technique without CPB was comparable with open approach in surgical and survival outcomes. However, due to the small sample size and selection bias, we should be more tempered in this conclusion.…”
Section: Discussionmentioning
confidence: 94%